Jump : dare to do what scares you in business and life - Perell, Kim (HarperCollins Leadership, an imprint of HarperCollins, 2021)
"Discover the simple, successful formula for facing your fears and finding the courage to Jump into the next chapter of your life. It's time to learn the approach that made serial-entrepreneur Kim Perell a multi-millionaire--and it could make you one too. In Jump, Kim shares her powerful personal story about when her career hit rock bottom and how she summoned the courage to take a life-changing leap into the unknown. Broke, bankrupt, and afraid, she learned how to trust her instincts and jump despite her fears."--Dust jacket flap.